Comunicación asertiva y la articulación de las funciones sustantivas Caso: Universidad Técnica Estatal de Quevedo - Zambrano Moreira, Roxana Monserrate (2020)
Correct communication is essential within higher education institutions for this reason the research work is presented in order to determine the degree of relationship between assertive communication and the articulation of substantive functions at the State Technical University of Quevedo, year 2019. To determine the objective described, surveys of teachers, administrative staff and students of the State Technical University of Quevedo were carried out in which it was possible to determine that although they mostly stated that they maintained a high assertiveness index at the time to initiate a communicative process it was also found that there is a percentage that expressed that the level of assertiveness in communication is not the best. The institution of higher education does not have the necessary mechanisms to improve relations between those who are part of it and optimize the tasks that are performed in the university, to try to solve this problem as a plan is carried out of training on the management of communication assertiveness by giving it the necessary tools to improve communication.